Peningkatan Hasil Belajar Siswa KELAS III SDN 107396 Paluh Merbau dengan Model PJBL pada Materi Yesus Memberi Makan Lima Ribu Orang dengan Berbantuan Media Kolase - Ezra Eliezer Situmorang; Yohanes Subasno; Veronika Sunarningsih (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to understand and improve the learning outcomes of Catholic Religious Education at SDN 107396 Paluh Merbau, Percut Sei Tuan District, Deli Serdang Regency. The study applies the Project-Based Learning (PjBL) model in the lesson about Jesus feeding five thousand people, utilizing collage media as a teaching aid.The researcher used a descriptive qualitative approach and data collection methods with quantitative observation techniques. In facing the 21st century and the Industrial Revolution 5.0, educators are required to adapt to significant changes and advancements in knowledge. Therefore, educators must be able to compete not only in terms of intelligence but also creativity and innovation in finding alternative learning methods. One such method that facilitates students to create individually or in groups is project-based learning, which is aligned with the process standards that encourage students to produce contextual works, both individually and collectively.One effort teachers can make is to implement innovative learning models, such as the Project-Based Learning (PjBL) model. This learning model serves as a breakthrough in revitalizing what is often monotonous and rigid learning, particularly at the elementary school level. Students in Phases A, B, and C are active and have a high level of curiosity. By applying the PjBL model at these phases, students can experience learning that satisfies their curiosity and stimulates their creativity